The moderating effect of cultural congruence on the internal marketing practice and employee satisfaction relationship: An empirical examination of Australian and Taiwanese born tourism employees - Huang, Yu-Ting; Rundle-Thiele, Sharyn (Tourism management (1982), 2014)
The role of internal marketing on building employee satisfaction has been empirically established. More than 200 internal marketing studies are evident in the literature yet few consider the role of an employee's own cultural background with no quantitative exploration to date. In response to this gap in the literature, this research seeks to understand whether cultural congruence (the degree to which an organisation meets an employee's cultural needs) moderates the internal marketing practice and employee satisfaction relationship in a culturally diverse work setting. A sample of 458 valid responses was received from English and Traditional Chinese online and face to face surveys of tourism employees in Australia who were both Australian and Taiwanese born. The data were analysed using confirmatory factor analysis and multi-group analysis. The results confirmed the positive internal marketing and employee satisfaction relationship. Further, this research contributes both applied and theoretical outcomes with empirical evidence establishing that cultural congruence can further strengthen the internal marketing and employee satisfaction relationship. Limitations and future research directions are outlined. •A person's own cultural background on internal marketing (IM) has received limited research focus.•Internal marketing leads to Australian and Taiwanese tourism employee satisfaction (ES).•Companies can improve the IM-ES relationship by catering to employees cultural needs.